The onset of phase transitions in condensed matter and relativistic QFT - Rivers, R.J.; Kavoussanaki, E.; Karra, G. (Condensed Matter Physics, 2000)
Kibble and Zurek have provided a unifying causal picture for the appearance of topological defects like cosmic strings or vortices at the onset of phase transitions in relativistic QFT and condensed matter systems respectively. There is no direct experimental evidence in QFT, but in condensed matter the predictions are largely, but not wholly, supported in superﬂuid experiments on liquid helium. We provide an alternative picture for the initial appearance of strings/vortices that is commensurate with all the experimental evidence from condensed matter and consider some of its implications for QFT.